Paranoia And Ambiguity In Before I Fall By Lauren Oliver: Postmodernism Study - Muhammad Maftukhan (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
The concern of the study is the paranoia and ambiguity as a social phenomenon experienced by the main character in Before I Fall by Lauren Oliver. It intended to examine the author’s narration and also the main character’s utterances which are portraying as a paranoia and ambiguity condition and the main character’s way to solve her problem of life.This study applies qualitative research, because the data are in the form of words or sentences. It examines  the  characters  utterances  and  author’s  narration  from postmodernism approach concerning on Jean Francois Lyotard’s postmodernism theory. In addition, data reduction, data displays, and conclusion drawing/verification are the techniques of analyzing the data.The result of the study finds paranoia and ambiguity as the theme of postmodern literature in Before I Fall by Lauren Oliver which faced by the main character, Samantha Kingston. The study also finds the main character’s way to solve her paranoia and ambiguity as her problem of life.